TERRITORIAL TRANSFORMATION AND SUSTAINABILITY IN SAN JUANITO (META): THE ARTICULATING ROLE OF BEAN CROPS - Garzon, Hernando Castro –; Salcedo Parra, Octavio José; Rodríguez Miranda, Juan Pablo (International Journal of Aquatic Research and Environmental Studies, 2026)
.